Aplikasi Simpan Kartu Nama dengan QR Code Berbasis Android - Agus Fatulloh; Muhammad Syafiq (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2020)
Currently, when you want to save someone's contact via a business card, it's still done manually, by entering one by one the data from the name card into the cellphone. This is very impractical and quite time consuming. Not to mention the risk that occurs when the data entered is wrong, due to errors in inputting to the cellphone. So we need an application that can help speed up the process of saving contacts from business cards.SIKANA is a mobile application that has a function to save someone's contact by scanning a business card or QR Code. The purpose of making this application is to simplify and speed up the process of saving contacts from business cards.